A Model of Layoff, Search and Job Choice and Its Estimation - Khandker, Rezaul K. (The Review of Economics and Statistics, 1992)
A labor-market model of search and transitions is analyzed where certain jobs carry layoff prospects and others do not. The dynamic value functions are solved for reservation wages for searchers with a choice between these jobs. For the laid-off worker, the wage at the prior job emerges as an important determinant of the optimal search strategy. Similarly, prospect of layoff is an important consideration for permanently separated workers during search. Conditioning on the nonparametric estimates of the reservation wages, the model is estimated using data from the Employment Opportunities Pilot Project survey. Copyright 1992 by MIT Press.